Implications of Anaphylaxis Following mRNA-LNP Vaccines: It Is Urgent to Eliminate PEG and Find Alternatives - Jinxing Song; Dihan Su; Hongbing Wu; Jeremy Guo (Pharmaceutics)
The mRNA vaccine has protected humans from the Coronavirus disease 2019 (COVID-19) and has taken the lead in reversing the epidemic efficiently. However, the Centre of Disease Control (CDC) reported and raised the alarm of allergic or acute inflammatory adverse reactions after vaccination with mRNA-LNP vaccines. Meanwhile, the US Food and Drug Administration (FDA) has added four black-box warnings in the instructions for mRNA-LNP vaccines. Numerous studies have proven that the observance of side effects after vaccination is indeed positively correlated to the level of anti-PEG antibodies (IgM or IgG), which are enhanced by PEGylated preparations like LNP vaccine and environmental exposure. After literature research and review in the past two decades, it was found that the many clinical trial failures (BIND-014, RB006 fell in phase II) of PEG modified delivery system or PEGylated drug were related to the high expression of anti-PEG IgM and IgG. In the background of shooting multiple mRNA-LNP vaccines in billions of people around the world in the past three years, the level of anti-PEG antibodies in the population may have significantly increased, which brings potential risks for PEG-modified drug development and clinical safety. This review summarizes the experience of using mRNA-LNP vaccines from the mechanism of the anti-PEG antibodies generation, detection methods, clinical failure cases of PEG-containing products, harm analysis of abuse of PEGylation, and alternatives. In light of the increasing prevalence of anti-PEG antibodies in the population and the need to avoid secondary injuries, this review article holds greater significance by offering insights for drug developers. It suggests avoiding the use of PEG excipients when designing PEGylated drugs or PEG-modified nano-formulations and provides references for strategies such as utilizing PEG-free or alternative excipients.